Randomized Control Trial Baseline Data on Use of Improved Efficient Cookstoves in Mozambique - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This survey was conducted to collect baseline data for a randomized control trial preceding the introduction of improved energy cookstoves in the Angonia district in Mozambique. A similar baseline study was also conducted in Malawi in the district of Dedza. Angonia district in Mozambique was selected because it shares a transboundary with the Dedza district in Malawi and has similar biophysical and socioeconomic conditions. This selection was intended because the project was set out to examine how differences in policies in the two countries contributed to the adoption and use of improved cookstoves under a randomized control trial experiment. The data also includes a section on discrete choice experiments that test several price subsidy policy options and their impact on the possible uptake of improved cookstoves. The data also includes another section again on discrete choice experiments testing fertilizer subsidy policy options and how they could impact on the uptake of agroforestry.